Evaluación de los factores determinantes del desarrollo agroindustrial en la región de San Martín - Sandoval Centa, Omar Alonso (2008)
The present work seeks to sensitize to near a new focus for the development of the region, having like base the agroindustrial activity, considering the current situation and the future conditions. lt looks for new alternatives generated under a new vision and looking for a favorable position of the regional agroindustry, evaluating the decisive factors of the regional development, and having as hypothesis that the current situation of the agroindustry, is a potential for the development of the region San Martin. As study environment to generate the proposals of strategies has been considered the region San Martin, for that which tools were used of diagnostic, evaluation and of plannThe region San Martin has favorable basic factors for the development of the agroindustry like they are: floors and appropriate climates, productive potential and biodiversity, these give us a comparative advantage in front of other regions, but we also have limitations like: manpower not qualified, scarce security, faulty access road, scarce matter prevails local for the agroindustry and faulty basic services. The agroindustrial managers have low asociatividad culture, disloyal competition exists as for prices; this rivalry added to a production of small scale, without suppliers of inputs, faulty strategies commercial, limited technology use and scarce relationship among support organisms that promote the development of the sector, doesn't favor to the development of the agroindustrial activity and the power of negotiation of the local offer that allows to have better margins of utility diminish. The Internet like support industry, opens possibilities for the identification of markets; but it limits us the scarce development of agroindustrial products, that they are not developed by not counting with: infrastructure of cold, certificate of quality of products, machinery and appropriate technology for their processThe main economic activity in the region is the agriculture, that which is the base for the development of the regional agroindustry, however for factors like capital, risk of the investment and political not very clear for its development, the regional economy is a primary economy, based on the marketing of agricultura! products. You should invest in infrastructure, and to identify technologies agroindustrial key to develop the productive complexes and foment their adaptation to the local reality, through political of development to the investigation and development. Far what, the development of the agroindustrial sector will depend it is guided the politicians of the regional development in an endogenous effort, and of the facility of how this industry adapts to the new markets (TLCs), with products with advantages in costs and differentiation.